BASIC TEACHING SKILL OF BALINEES COUNSELOR AT BANJAR DISTRIC BULELENG REGENCY - Dewi, Ni Luh Degeng Ratna; Putrayasa, Ida Bagus; Paramartha, I Ketut (Universitas Pendidikan Ganesha, 2019)
This researche aimed at (1) describing basic skill of Balinees counselor at Banjar distric, Buleleng regency, (2) The problem in implementing basic skill of Balinees counselor, (3) The factor causing the problem in implementing basic skill of Baliness councelor, (4) The solution describing based on the real factors in implementing basic skill of Balinees coubselor in learning procces. The design of this research is descriptive qualitative. The sample were 12 people of Balinees counselor from Buleleng regency. Data collection technique used interviewing and observation. The analysis of data was started from data reduction, proccessing/displaying, and given solution. The results of this research was most of the Balinees counselor did not apply basic skill of teaching to teach Balinees language efficiently and maximally. It was proven with (1) the diffuculty of the Balinees counselor in mastering the content of learning as a result they were difficult to teach the content of Balinees language to the learner in learning procces. (2) Lack of interest of the learning to deeply learn about Baliness language. (3) Lack of facilities in supporting Baliness counselor in teaching as a result they got a difficulty in sharing knowledge to the learner. The solution given by the researcher were staurted from variating technique of teaching of Baliness to learner in learning procces, being discipline in mastering class or atmosphere of the class during learning procces. In addition, the researcher provided correlative media in implementing basic skill of Baliness counselor. In summary, the result of this research done was not effective.